Новые восточнопалеарктические виды наездников-ихневмонид рода Phytodictus Gгav. (Hymenoptera, Ichneumonidae) - Толканиц, В.И. (Вестник зоологии, 1976)
Two new species of the genus Phytodietus Cray are described: P. (Neuchorus) kunashiricus sp. n. (Kunashir isl.) and P. (Neuchorus) decoratus sp. n. (Chita and Amur Regions). A key is given for determination of Neuchorus subgenus species known for the USSR.